A construção do controle por estímulos condicionais sobre o comportamento verbalmente controlado - Barrelin, Evelyn Christina Peres (2008)
Insensibility has been referred as the persistency of a response pattern despite changes on the contingencies. Conditional control over the instructional contingencies has been mentioned as one of the possible variables responsible for this performance, in negative reinforcement contingencies. The present work aimed to put verbally-governed behavior under stimulus control and evaluate its effect over posterior performances, in the presence of these same stimuli. 18 undergraduate students participated in a computer game (16 on Experiment 1 and 2 on Experiment 2), which was based on a trial procedure. On each trial, the student had to click on a button for 3 seconds to be reinforced (points changed for tickets to run on a draw). In the Experiments 1 and 2, the experimental variables manipulated were: the instructions, the reinforcement schedules and the colors of the screen. In the baselines (Phases 1, 3 and 5), there was no instruction, the color screen was blue and a rate of 4 to 9 responses/3s was followed by reinforcement. In Phase 2, the rules press several times and press few times , the DRL and interval DRH reinforcement schedules (of which response rate required were from 1 to 3/3s and 10 or more/3s, respectively) and the orange and green screen colors were combined. The orange color was paired with consistency between rule and schedule and the green color was paired with inconsistency between them (or the opposite, depending on the group). This phase was terminated when a stability criterion had been reached in each component. In Phase 4, a minimal rule and the requirement of a 4 to 9r/3s rate were presented together with the green and orange screen colors. Finally, in Phase 6, participants were distributed in two groups that differed from the programmed reinforcement schedule (interval DRL or interval DRH), but not from the rules ( several times and few times ) and screen colors (orange and green). In Experiment 2, Phases 4 and 5 of the Experiment 1 had been excluded and a minimum number of alternations between the colors of the screen, instructions and schedule in Phase 2 was established. The results of both experiments, among others things, suggest: (a) the relevance of a minimum number of alternations between components in Phase 2, as a facilitated condition for the establishment of conditional control of the colors of screen on the instructional contingency; (b) persistence of the instructional control, when considered the first trial of a component; (c) immediately previous history of coherence and incoherence between schedule and instruction as conditional stimulus in relation to the verbally-governed behavior; and (d) the production of two distinct pattern responses, due to the schedules in use, that tended to alternate, in Phase 2, depending on the consequences produced in the first trial of a component